Physico-Chemical Characterization and Biopharmaceutical Evaluation of Lipid-Poloxamer-Based Organogels for Curcumin Skin Delivery - Vigato, Aryane Alves; Querobino, Samyr Machado; de Faria, Naially Cardoso; Candido, Ana Carolina Bolela Bovo; Magalhães, Lizandra Guidi; Cereda, Cíntia Maria Saia; Tófoli, Giovana Radomille; Campos, Estefânia Vangelie Ramos; Machado, Ian Pompermayer; Fraceto, Leonardo Fernandes; de Sairre, Mirela Inês; de Araujo, Daniele Ribeiro (Frontiers in Pharmacology, 2019)
Organogels (ORGs) are semi-solid materials, in which an organic phase is immobilized by a three-dimensional network composed of self-organized system, forming the aqueous phase. In this context, lipid–Pluronics (PLs) organogels form a two-phase system which can be effectively used as skin delivery systems, favoring their permeation across the skin. In this study, we presented the development of ORGs skin drug-delivery systems for curcumin (CUR), a liposoluble phenolic pigment extracted from the turmeric rhizome. In special, we designed the formulations compositions in order to carry high amounts of CUR soluble in oleic acid (OA), as organic phase, entrapped into an aqueous phase composed of micellar PL-based hydrogels by associating two polymers with different hydrophilic-lipophilic balances, Pluronic F-127 (PL F-127) and Pluronic L-81 (PL L-81), to enhance the permeation across the skin. Results revealed that the incorporation of PL L-81 favored the CUR incorporation into micelle-micelle interface. CUR insertion into OA-PL F-127/L-81 reduced both G’/G” relationship ( 16 x) and viscosity values (η* 54 mPa.s, at 32.5 °C), disturbing the ORGs network structural organization. In vitro permeation assays through Strat-M® skin-model membranes showed that higher CUR permeated amounts were obtained for OA-PL F-127/L-81 (4.83 µg.cm-2) compared to OA-PL F-127 (3.51 μg.cm−2) and OA (2.25 μg.cm−2) or hydrogels ( 1.2 μg.cm−2, p < 0.001). Additionally, ORGs formulations presented low cytotoxic effects and evoked pronounced antileishmanial activity (IC50 < 1.25 µg.mL-1), suggesting their potential use as skin delivery systems against L. amazonensis. Results from this study pointed out OA-PL- based ORGs as promising new formulations for possible CUR topical administration.